PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DIGITAL TERHADAP KREATIVITAS DAN MOTIVASI BELAJAR SISWA - Ahmad Iqbal; Mustafa; Syamsu A Kamaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the influence of digital entrepreneurship learning on enhancing students' creativity and learning motivation in the digital era. The background arises from the need for education systems to adapt to technological advancements and labor market demands. Digital entrepreneurship learning integrates technology with entrepreneurial practices to foster students' creativity, innovation, and independence. The research method employs a qualitative descriptive approach using library research to analyze relevant literature. The findings reveal that digital entrepreneurship learning positively contributes to increasing creativity and learning motivation by enhancing students' attention, relevance, confidence, and satisfaction. This learning approach aids students in developing life skills that are adaptive to technological evolution and the modern business world. Keywords: digital entrepreneurship, creativity, learning motivation, education, digital era